Retracted: Tantangan Literasi Keislaman Siswa Madrasah Ibtidaiyah (MI) Dalam Perspektif Kajian Filsafat Pendidikan Islam - Moh. Nasep; Dini Permana Sari (Educate : Journal of Education and Learning, 2025)
RETRACTION NOTICE The article titled "Challenges of Islamic Literacy for Elementary Madrasah (MI) Students from the Perspective of Islamic Educational Philosophy Studies" by Moh. Nasep and Dini Permana Sari, published in Educate: Journal of Education and Learning on December 20, 2025, has been retracted. Publication link: https://jurnal.dokicti.org/index.php/educate/article/view/1454. The retraction was made at the author's request after double submission/double publication was discovered. The same article was also published in English under the title "The Challenges of Islamic Literacy of Madrasah Ibtidaiyah Students From the Perspective of the Study of Islamic Education Philosophy" in the International Journal of Islamic Religious Education (JPAII) on December 21, 2025. Publication link: https://cahaya-ic.com/index.php/JPAII/article/view/2445. An investigation by the Educate: Journal of Education and Learning editorial team, along with the management of CV. Doki Course and Training, confirmed that this action constituted a violation of academic ethics. Therefore, the article was officially withdrawn from publication to maintain scientific integrity and ethical publishing standards.